Đo tự động nồng độ clor trong nước - Thoa, Pham Huy; Phu, Dang Thanh; Cat, Pham Thuong (Journal of Computer Science and Cybernetics, 2018)
For controlling a quality of water, an automatical apparatus for measuring density of clor in the water is constructed and tested. This apparatus functionates on the basis of optoelectrical principle. It can functionato auto maticall and semi-automatically. The measuring process of the apparatus is controlled by a system of mP. The measuring result is displayed in the display and is printed in the teletype. An acoustic alarm is signalired when the measuring result lies over the value determinate.